"Strachy na lachy"? Groza w kryminałach retro Marka Krajewskiego i Marcina Wrońskiego = "Em pty Threats?" Horror in Retro crime novels by Marek Krajewski and Marcin Wroński - Głąb, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Marek Krajewski`s and Marcin Wroński`s novels cannot be classified as horror stories. In spite of this, it is inaccurate to say that the horror present in them is merely an unreal way to inspire fear. Those novels offer a fictional "playing with danger or fear" to their readers. Because of that, the reader can experience spaces which are unavailable or unique, feeling the so called "safe fear" - a kind of unreal fear or a substitute for genuine fear.
Keywords: powieść kryminalna retro; Krajewski, Marek (1966- ) - twórczość; Wroński, Marcin (1972- ) - twórczość